2021
DOI: 10.1002/oby.23279
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow adipose tissue content in Latino adolescents with prediabetes and obesity

Abstract: Objective This study aimed to examine whether total, regional, and organ fat predicts bone marrow adipose tissue (BMAT) fat content and to explore whether BMAT fat content differs by sex among Latino youth. Methods Latino youth (n = 86; age 13.6 [1.4] years, 62% male) with obesity (BMI percentile = 98.5% [1.2%]) underwent a dual‐energy x‐ray absorptiometry scan to assess body composition and a magnetic resonance imaging scan to determine abdominal adiposity, liver fat, and vertebral BMAT fat content in the tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Latino male adolescents have higher BMAT in their lumbar and thoracic BM than females, which increases with visceral obesity 101 . Early‐pubertal girls in the USA also show this body fat and BMAT association 102 .…”
Section: Obesity Impacts Bm Adiposity Lymphopoiesis and Myelopoiesismentioning
confidence: 93%
“…Latino male adolescents have higher BMAT in their lumbar and thoracic BM than females, which increases with visceral obesity 101 . Early‐pubertal girls in the USA also show this body fat and BMAT association 102 .…”
Section: Obesity Impacts Bm Adiposity Lymphopoiesis and Myelopoiesismentioning
confidence: 93%
“…Specifically, Newton et al [19] assessed body composition in 59 earlypubertal girls and found a positive association between body fat and BMAT. Another study conducted in Latino adolescents found that greater BMAT content was positively associated with liver fat and visceral adipose tissue [20]. Conversely, BMAT accumulation was negatively correlated with bone strength in anorexia nervosa patients [21].…”
mentioning
confidence: 96%